Matrix metalloproteinase-2 is elevated in midtrimester amniotic fluid prior to the development of preeclampsia - Daniel-Spiegel Etty; Goldman Shlomit; Lavee Michal; Shalev Eliezer (BMC, 2009)
Abstract Objective To evaluate levels of matrix metalloproteinases (MMP) and their inhibitors (TIMP) in second trimester amniotic fluid of women with hypertensive disorders compared to normotensive women. Study Design Amniotic fluid was obtained from 133 women undergoing genetic second trimester amniocentesis. Zymography was performed for MMP characterization and an MMP-2 ELISA kit was used to determine MMP-2 levels. TIMP-2 expression was evaluated using western blot. Results Mean amniotic fluid MMP-2 and TIMP-2 levels were significantly higher in women who developed a hypertensive disorder compared to normotensive women (P < 0.0004 and P < 0.01, respectively). When subdivided into subgroups, amniotic fluid from women who eventually developed preeclampsia or superimposed preeclampsia showed significantly higher MMP-2 levels than normotensive women (P < 0.05). However, no statistical difference in MMP-2 levels was found between patients with gestational hypertension and normotensive patients. Conclusion Higher amniotic fluid MMP-2 and TIMP-2 levels are found in women who eventually develop preeclampsia.